Фразеологічні одиниці сучасної англійської мови на позначення динаміки конфлікту - Коляда, Еліна Калениківна; Koliada, E. К. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті здійснено спробу виявити англійські фразеологічні одиниці, що позначають динаміку конфлікту. Конфлікт передбачає усвідомлення того, що інтереси однієї людини, потреби або цінності несумісні з інтере¬сами іншої. Конфлікти виявляються через дії сторін, які варіюють від слів до насильства. Люди по-різному ставляться до конфлікту. Ці відносини впливають на їх поведінку в конкретних конфліктах. Деякі люди, зазвичай, намагаються уникнути конфлікту, а інші готові вступити в нього. Вирішення конфлікту пе¬редба¬чає переконання, що конфлікт закінчився, припинення конфліктної поведінки та впровадження нових форм поведінки. . In this article the attempt to reveal English phraseological units denoting conflict dynamics has been made. Phraseological units are word groups with a fixed lexical composition and grammatical structure. Conflict is regarded as a disagreement, a real or perceived incompatibility of interests, inconsistent worldviews, or a set of behaviours. Conflict involves the perception that one person’s interests, needs or values are incompatible with those of another person. Conflict also involves negative feelings. Conflict may be viewed as occurring along perception, emotional and action dimensions. Conflicts are manifested through the parties’ actions, from speech to violence. People have different attitudes toward conflict in general. These attitudes shape their behavior in particular conflicts. Some people tend to avoid conflict while others are willing to engage. Conflict resolutions involve believing the conflict is ended, no longer feeling in conflict, stopping conflict behavior and implementing new behaviors.
Phraseological Units Denoting Conflict Dynamics in Modern English
Keywords: фразеологічна одиниця; phraseological unit; конфлікт; conflict; учасники; parties